Traditional chinese medicine pattern classification and herbal medicine for COVID-19: A comparative study of data from different sources - Zhen Gao; Ying-Ying Liu; Ye-Meng Chen; Jing-Cheng Dong (World Journal of Traditional Chinese Medicine, 2023)
Background: Traditional Chinese medicine (TCM) plays a crucial role in the prevention and control of coronavirus disease 2019 (COVID-19). Objective: The study aimed to reveal the distribution characteristics of COVID-19 TCM syndrome types and syndrome elements and the law of TCM treatment and medication. Methods: The TCM diagnosis and treatment protocol for COVID-19 and clinical research data were obtained through network retrieval, and Revman 5.3 and SPSS 23.0 were employed to analyze the composition of TCM syndromes and the situation of TCMs in meta and frequency. Results: The top three TCM syndromes of COVID-19 included damp-heat accumulation in the lung pattern, damp abundance due to spleen deficiency, and epidemic toxin invading the lung pattern, while the syndrome elements were dampness, heat, and toxin. Gypsum fibrosum, Pogostemonis herba, and Armeniacae semen were identified as the commonly used drugs. Different syndrome elements were identified at lung disease location: Forsythiae fructus, Glycyrrhizae radix, and Armeniacae semen can be used for “wind;” Glycyrrhizae radix, Armeniacae semen, and Scutellariae radix can be used for “Heat;” Armeniacae semen, Sheng Gypsum fibrosum, and Ephedrae herba can be used for “Toxin;” Ephedrae herba, Armeniacae semen, and Atractylodis rhizome can be used for “Damp;” Magnoliae officinalis Cortex, Ephedrae herba, and Zingiberis Rhizoma recens can be used for “cold;” and Armeniacae semen, Gypsum fibrosum, Ephedrae herba, and Lepidii/Descurainiae semen can be used for “epidemic.” Conclusion: The establishment of a treatment scheme based on the classification of disease syndrome elements should be considered for sudden infectious diseases, such as COVID-19. Pogostemonis herba, Armeniacae semen, Gypsum fibrosum, and Glycyrrhizae radix should be considered as effective drugs from TCM for the treatment of COVID-19.